PENANAMAN NILAI ANTIKOROUPSI BAGI MAHASISWA FIS UNNES MELALUI MATA KULIAH PENDIDIKAN ANTI KORUPSI - Kristiono, Natal (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2018)
The purpose of this study was to determine the success of the implementation of Anti-Corruption Education lectures. One indicator of success, namely after participating in Anti-Corruption education students can afford anti-corruption education, among others, to know the dangers of corruption. can understand anti-corruption values. character change. The factors that support the success of anti-corruption education are self-awareness factors, media and learning resources and the selection of appropriate strategies. Factors that hinder the success of anti-corruption education are environmental factors and mistakes in choosing the media and learning strategies.